Programa de entrenamiento adaptado a las necesidades de aprendizaje de dos deportistas con discapacidad intelectual y trastorno del espectro autista pertenecientes a la selección paralímpica de Tuluá, enfocado en el mejoramiento de la eficiencia de brazada de la técnica de libre (2020)
Over the years, disability has achieved a very important conceptual evolution, although there is still a long way to go, it must be recognized that this evolution has contributed to increase the participation of the people who are a part of this population in many social spheres, gradually approaching the ideal of equity and therefore, the real guarantee of their rights. In the sports field, moving forward from its use only with a therapeutic purpose, adapted sports have increased more and more, offering their contribution to the mentioned ideal from the competitive point of view; Accordingly, the purpose of this research is Adapted Swimming, applied particularly with two people with intellectual disabilities diagnosed with Mild Autism Spectrum Disorder, who belong to the Paralympic Swimming Team of the municipality of Tuluá. In this way, the present case study was presented from a quantitative approach, accompanied with a quasi-experimental design with an explanatory scope, which was aimed to determine the incidence of a training program adapted to the learning needs of the sample, determined as the proposed research program, about the stroke efficiency in the free technique of the two athletes. Based on the longitudinal section of the study, which allowed the realization of a pretest and a posttest at the initial and final moments of the intervention and its subsequent comparison, the obtained results highlighted mainly that even though the arithmetic mean presented a low decrease after the intervention, such statistical data indicates a relevant influence in the performed intervention, about the stroke efficiency in the front crawl of the sample. For this reason, the research concludes that the independent variable (adapted training program), did not present meaninful effects on the dependent variable (stroke efficiency of the front crawl) of the two swimmers who are a part of this case study, indicating from this that the study sustains the null hypothesis. To conclude, this research recommends for subsequent studies, the incorporation of other training models with longer duration, accompanied by other types of pedagogical strategies and tools, in order to positively affect the processes of athletes, and to continue contributing to the existent research need about the intervention models in general for this type of population, on the training ground in particular.